2020
DOI: 10.1371/journal.pone.0232398
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the microbiome of Ixodes scapularis and Amblyomma americanum

Abstract: The microbial community composition of disease vectors can impact pathogen establishment and transmission as well as on vector behavior and fitness. While data on vector microbiota are accumulating quickly, determinants of the variation in disease vector microbial communities are incompletely understood. We explored the microbiome of two humanbiting tick species abundant in eastern North America (Amblyomma americanum and Ixodes scapularis) to identify the relative contribution of tick species, tick life stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 63 publications
11
66
8
Order By: Relevance
“…In contrast to our results, three recent studies have shown no significant difference in bacterial diversity associated with Borrelia infection status [ 58 , 73 , 74 ], and a fourth study was ambiguous [ 28 ]. However, one of these studies reported results for a mix of females and males [ 73 ], which would have increased the variance in an already noisy system [ 17 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our results, three recent studies have shown no significant difference in bacterial diversity associated with Borrelia infection status [ 58 , 73 , 74 ], and a fourth study was ambiguous [ 28 ]. However, one of these studies reported results for a mix of females and males [ 73 ], which would have increased the variance in an already noisy system [ 17 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The microbiome of Ixodes scapularis ticks in Alberta is dominated by Rickettsia endosymbionts, with Pseudomonas more common in some individuals, making it similar to the microbiome composition reported for these ticks in established areas of their range [ 28 , 29 , 51 ]. Alberta ticks that carried Borrelia had significantly greater microbiome diversity than ticks that had no Borrelia , a finding that suggests an altered microbiome ecology in Borrelia -positive ticks, as well as the potential to use microbiome diversity as an indicator of elevated risk of infection by Borrelia .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Rickettsia endosymbionts are common in Ixodes and some Ornithodoros tick species, while FLEs have been found in Amblyomma , Dermacentor , and Hyalomma ticks [ 31 ]. However, the number of different endosymbionts and prevalence of endosymbionts in each tick are known to vary by geographic location, time of year collected, life stage, sex, tick species, and lab-reared vs. wild-caught ticks [ 31 , 101 , 102 , 103 , 104 ]. A comprehensive study of over 80 tick species from around the world, including lab-reared and wild-caught ticks, identified the most prevalent tick endosymbiont to be a Coxiella -like endosymbiont (CLE) [ 31 ].…”
Section: Tick Endosymbiontsmentioning
confidence: 99%